2015
DOI: 10.4028/www.scientific.net/amm.808.169
|View full text |Cite
|
Sign up to set email alerts
|

Custom Implants: Manufacturing Principles and Determination of Psychological Price

Abstract: This paper presents the basic principle for achieving a custom implant from biocompatible materials with the human body using Additive Manufacturing technologies. Due the fact that is a new product which will be introduced on the market, a marketing study was needed. This study presents also the mathematical, analytical and graphical modeling of the psychological price, for a custom implant type cranioplasty / hip prosthesis / spinal implant. The assessment of psychological price for a custom cranioplasty impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The armpit area was selected to develop a complex sweat glands module [1]. Regarding the AM possibilities, various scientific papers shown that 3D printing technologies can produce complex prototypes for different applications under the "layer by layer" principle [2][3][4][5][6][7][8][9][10][11]. Comparing with conventional manufacturing methods [12][13][14], 3D printing provides reduced time to market, lower product development costs, and improved design process [15].…”
Section: Introductionmentioning
confidence: 99%
“…The armpit area was selected to develop a complex sweat glands module [1]. Regarding the AM possibilities, various scientific papers shown that 3D printing technologies can produce complex prototypes for different applications under the "layer by layer" principle [2][3][4][5][6][7][8][9][10][11]. Comparing with conventional manufacturing methods [12][13][14], 3D printing provides reduced time to market, lower product development costs, and improved design process [15].…”
Section: Introductionmentioning
confidence: 99%
“…for each type of material tested for producing different types of customized medical implants by using this technology [10,11]. In order to determine the influence of the process parameters on the mechanical properties of the SLS parts, researchers have tried to use different approaches to obtain better results regarding the process [12]. Many researchers have varied the laser power or scanning speed and maintained constant the other parameters to determine their influence on the mechanical properties of the manufactured parts [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3]. This technological process offers a number of advantages over conventional manufacturing technologies, especially regarding to the possibility of producing complex models with high productivity and the use of cheap materials for manufacturing [4,5].…”
Section: Introductionmentioning
confidence: 99%